2021
DOI: 10.1016/j.eclinm.2021.100905
|View full text |Cite
|
Sign up to set email alerts
|

Higher dose docosahexaenoic acid supplementation during pregnancy and early preterm birth: A randomised, double-blind, adaptive-design superiority trial

Abstract: Background: Several meta analyses have concluded n-3 fatty acids, including docosahexaenoic acid (DHA), reduce early preterm birth (EPB, < 34 weeks), however, the amount of DHA required is unclear. We hypothesized that 1000 mg DHA per day would be superior to 200 mg, the amount in most prenatal supplements. Methods: This randomised, multicentre, double-blind, adaptive-design, superiority trial was conducted in three USA medical centres. Women with singleton pregnancies and 12 to 20 weeks gestation were eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Regardless, all studies require additional testing using cohorts enriched with 1 st trimester subjects since the efficacy of low-dose aspirin to prevent EOP is gestation-dependent. The successful identification of a predictive test for both sPTB and EOP would provide caregivers a single test that could identify asymptomatic women likely to develop one or more of the three most important pregnancy disorders, two which already have therapeutic options that may improve outcome [ 35 , 36 , 37 ]. Additionally, if any of the panels perform similarly to the current studies, they will be highly cost effective [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, all studies require additional testing using cohorts enriched with 1 st trimester subjects since the efficacy of low-dose aspirin to prevent EOP is gestation-dependent. The successful identification of a predictive test for both sPTB and EOP would provide caregivers a single test that could identify asymptomatic women likely to develop one or more of the three most important pregnancy disorders, two which already have therapeutic options that may improve outcome [ 35 , 36 , 37 ]. Additionally, if any of the panels perform similarly to the current studies, they will be highly cost effective [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Middleton et al highlighted the important contribution of the maternal intake of DHA in reducing the risk of preterm birth [ 38 ]. Accordingly, Carlson et al, in a multi-center, double-blind, randomized clinical trial, enrolled 1100 pregnant women between 12 and 20 weeks of gestation [ 39 ] and divided them into an experimental group that received 1000 mg DHA/day and a control group with 200 mg/day of DHA supplementation. At the end of the study, the authors concluded that women with a higher intake of DHA had a lower incidence of premature birth (<34 weeks) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Carlson et al, in a multi-center, double-blind, randomized clinical trial, enrolled 1100 pregnant women between 12 and 20 weeks of gestation [ 39 ] and divided them into an experimental group that received 1000 mg DHA/day and a control group with 200 mg/day of DHA supplementation. At the end of the study, the authors concluded that women with a higher intake of DHA had a lower incidence of premature birth (<34 weeks) [ 39 ]. These findings could be partly explained by the anti-inflammatory and immunomodulatory activity of DHA, which has already been widely investigated in previous studies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A first-of-its-kind study supported by NIEHS and NICHD found that unbalanced progesterone signals may cause some pregnant women to experience preterm labor or prolonged labor, and further suggests that progesterone receptors can be future therapeutic targets to prevent preterm birth (3). NICHD-supported scientists also recently established that a higher dose of docosahexanoic acid (DHA), an omega-3 fatty acid, is associated with lower early preterm birth rates, suggesting that screening DHA levels in pregnancy could be used as a tool to decrease risk of preterm birth (4).…”
Section: The Overall National Institutes Of Health Research Portfolio In Preterm Birthmentioning
confidence: 99%